Organization report:Private school of nursing at Karachi, Pakistan - Saleem Punjani, Neelam; Malik Bhanji, Sahreen (International Journal of Endorsing Health Science Research, 2014)
Nursing as a profession today still faces several challenges. There seems a dire need to produce such professional nurses that up bring the dignity of this distinct profession. The heavy responsibility of producing such professional nurses lies in the hands of nursing institutions and primarily the schools and colleges of nursing. The standard of the education offered by these institutions plays an important role in this regard. While addressing at the inaugural ceremony of the Aga Khan University School of nursing and midwifery, His Highness the Aga Khan, chancellor of the Aga Khan University spelt out the vision for the nursing profession in the following words “today, this is the beginning, the birth of a new medical institution in Pakistan, the Aga Khan University…and I hope, this day will also be the dawn of a new dimension for the profession of nursing in Pakistan”. Thus it is important that nursing institutions undergo continuous quality assurance process to maintain the high standards of nursing education to develop nurses that can claim their position in this challenging era.